BREAKING WAVE-FORCES ON HORIZONTAL CYLINDERS CLOSE TO THE SEA-BED - YUKSEL, Y; NARAYANAN, R (ELSEVIER SCIENCE BV, 1994)
Experimental data concerning the breaking wave forces exerted on two horizontal cylinders are reported. The magnitudes of the forces are the largest at the plunge point. Some differences in the details of the force traces at the plunging and the breaking points are observed. The peak value of the breaking-wave force varies from one wave cycle to another. The horizontal and the vertical forces at the breaking and the plunge points for the two cylinders are brought together by considering the wave heights at those points.
Keywords: VERTICAL CYLINDERS; VELOCITY; Engineering